A CASE REPORT OF POLAND SYNDROME TREATED FOR SYNDACTYLY RELEASE AT KHYBER TEACHING HOSPITAL PESHAWAR (Journal of Medical & Health Sciences Review, 2025)
Background: Poland syndrome (PS) is a rare congenital condition characterized by unilateral absence or underdevelopment of the pectoralis major muscle, often accompanied by ipsilateral hand anomalies such as syndactyly. The syndrome is more common in males, predominantly affecting the right side. Severity and associated anomalies vary widely, making early diagnosis and appropriate intervention essential.Case Presentation: We report a case of a 16-year-old right-hand dominant male from a rural area of Peshawar, presenting with congenital webbing (syndactyly) of the index, middle, and ring fingers of the right hand. Clinical examination revealed an absent right pectoralis major muscle. Due to financial constraints, confirmatory imaging (CT scan) was not performed. The patient underwent successful surgical release of syndactyly between the middle and ring fingers. A second-stage release of the index and middle fingers was planned for a later date. There was no family history of PS, and no cardiac or other systemic anomalies were detected.Discussion: Poland syndrome exhibits diverse phenotypic variability. This case aligns with the classical presentation in males, involving right-sided chest wall and upper limb anomalies. The absence of systemic involvement and mild severity allowed functional and aesthetic improvement via surgical intervention. Literature suggests vascular disruption during embryogenesis as a likely pathophysiological mechanism. Timely surgical correction in such patients enhances hand function and cosmetic outcomes, especially in cases with syndactyly.Conclusion: This case highlights a mild variant of Poland syndrome involving functional impairment due to syndactyly, treated successfully at a tertiary care hospital in Pakistan. It emphasizes the importance of clinical evaluation for timely diagnosis and intervention, especially in resource-limited settings where imaging may not be feasible. To our knowledge, this is the first reported case of PS managed surgically in our institution.